Chapter Between Adoption and Assimilation: The Case of Ištar of Ḫattarina - Barsacchi, Francesco Giuseppe (Studia Asiana, 2023)
In his investigation of the expansion of the cult of the "deity of the night" in Anatolia and her relationship with Ištar (Studien zu den Boğazköy-Texten 46, 259-439), J. Miller exposed the complexity of a diachronical analysis of the religious phenomenon represented by the diffusion of local "forms" or "aspects" of Ištar during the late Hittite period. However, many relevant issues concerning the role of the goddess in the Hittite dynastic pantheon, heavily influenced by Ḫurrian beliefs, and her presence in local pantheons, are still to be dealt with. As a case study, the present contribution will focus in particular on the goddess Ištar of Ḫattarina, attested together with the "Kanešite gods" Pirwa and Aškašepa in Muwatalli II's prayer CTH 381. This unusual association may be derived from the interpretation of a local female deity traditionally defined as MUNUS.LUGAL, "queen" in Hittite local pantheons, as a form of Ištar.